Holocene multi-proxy analyses from Lake Fazilman, Uzbekistan: pollen, NPPs, GDGTs, XRF, magnetic susceptibility, climate and vegetation quantitative reconstructions - Lucas Dugerdil; Guillemette Ménot; Odile Peyron; Dilfuza Egamberdieva; Isabelle Jouffroy-Bapicot; Boris Vannière; Jakhongir Alimov; Elise Luneau; Johanna Lhuillier; Sébastien Joannin (PANGAEA, 2025)
Holocene climate and vegetation reconstructions become mandatory to improve model reliability and access climate change consequences on human societies. This data set presents the first Holocene-scale, multi-proxy palaeoenvironmental reconstructions and raw data from Lake Fazilman, located in Uzbekistan, at the ecotone between steppe and forest. Lake Fazilman (Fazilman kul, 40.550406 N, 66.589361 E; 1637 m a.s.l.) is a piedmont lake located in the Nuratau range at the junction of Navoi and Samarkand provinces. The sediment core was collected in July 2021 at Lake Fazilman. A 227 cm-long core was retrieved from a stable vegetated island using a 50 cm Russian corer. This data set contains all raw data and reconstructions provided from the Lake Fazilman: X-Ray Fluorescence, inorganic geochemistry, isoprenoid and branched Glycerol Dialkyl glycerol Tetraethers, pollen and non-pollen palynomorphs counts and pollen-based paleoclimate and paleoenvironemental reconstructions. From the brGDGT and pollen data, quantitative climate reconstructions were provided using ensemble modelling. For each dataset, the sample depth is given in centimeter and the age in year calibrated BP (age-depth model performed with BACON and the IntCal20 calibration curve based on 15 radiocarbon dating).